The impact of working capital, business location, and information technology on the income level of SMEs in Jayapura Regency - Margaretha Kere; Anita Erari; Quinci Fransiska (Magister Manajemen Universitas Cenderawasih, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in the regional economy, yet the determinants of their income in eastern Indonesia remain understudied. This study aims to analyze the effect of business capital, business location, and information technology on the income level of MSMEs in Jayapura Regency, both partially and simultaneously. A quantitative approach was employed with 100 respondents selected through proportionate stratified random sampling from a population of 2,653 MSME actors. Data were collected using a Likert-scale questionnaire and analyzed through multiple linear regression with SPSS version 25. The results show that business capital (β = 0.265; Sig. 0.040), business location (β = 0.292; Sig. 0.037), and information technology (β = 0.315; Sig. 0.007) each have a positive and significant effect on income level. Simultaneously, the three variables have a significant effect (F = 21.917; Sig. 0.000) with an Adjusted R² of 0.388. Information technology has the largest contribution in the model. The study concludes that improving MSME income is associated with the combination of capital, location, and information technology, with digitalization as a priority for MSME empowerment policy in Jayapura Regency.